2018
DOI: 10.1108/et-12-2017-0196
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of out-of-class communication through instant messaging

Abstract: Purpose -Despite the growing body of literature demonstrating the role of communication in educational settings, there are limited up-to-date studies exploring the use of an Instant messaging (IM) tool and its impacts on students' learning outcomes, especially in the tertiary education in Vietnam. This study approached instant messaging as an out-of-class communication (OCC) approach in computer-mediated communication (CMC). The aim of this study was to investigate students' perceived quality of information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…A recent meta-analysis of teacher-student out-of-class communication, examining studies that span over a few decades and cover altogether thousands of students, had revealed positive effects of such communication on both affective and (perceived) cognitive learning (Goldman, Goodboy, & Bolkan, 2016). Similar findings have been recently found regarding teacherstudent communication that is facilitated via instant messaging apps (Hershkovitz, Abu Elhija, & Zedan, 2019;Nkhoma, Thomas, Nkhoma, Sriratanaviriyakul, Truong, & Vo, 2018). Indeed, one of the most prominent characteristics of instant messaging-that is, immediacy-has been repeatedly indicated as an important factor of positive teacher-student communication via digital platforms (e.g., Hershkovitz & Forkosh-Baruch, 2019;Rosenberg & Asterhan, 2018).…”
Section: Introductionsupporting
confidence: 59%
“…A recent meta-analysis of teacher-student out-of-class communication, examining studies that span over a few decades and cover altogether thousands of students, had revealed positive effects of such communication on both affective and (perceived) cognitive learning (Goldman, Goodboy, & Bolkan, 2016). Similar findings have been recently found regarding teacherstudent communication that is facilitated via instant messaging apps (Hershkovitz, Abu Elhija, & Zedan, 2019;Nkhoma, Thomas, Nkhoma, Sriratanaviriyakul, Truong, & Vo, 2018). Indeed, one of the most prominent characteristics of instant messaging-that is, immediacy-has been repeatedly indicated as an important factor of positive teacher-student communication via digital platforms (e.g., Hershkovitz & Forkosh-Baruch, 2019;Rosenberg & Asterhan, 2018).…”
Section: Introductionsupporting
confidence: 59%
“…They might be scholars whose research is interdisciplinary, and thus, they have publications in topics that blend education and another field (for instance, see Tran, Trinh, et al ., 2019; Vuong et al ., 2018). Besides, they might also be an officer who is working for a public agency in charge of education administration (for instance, see Hayden & Lam, 2007) or those who work for non‐governmental organizations (Nkhoma et al ., 2018; Phelps, Graham, Ha, & Geeves, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regard to marketing teaching and learning strategies, the writings have reached: The importance of communication outside the classroom to improve learning (Nkhoma et al, 2018) ,as it improves social cohesion between students and their teachers, with the availability of asking questions about the subjects of the course, and improving their independence of study skills. Kapasi and Grekova (2018) also indicated the importance of involving students in the learning process through continuous feedback from students represented in (short surveys on issues that students find more or less related to marketing decisions), encouraging discussions and increasing their quality and measured in depth of answers, that students provide during those discussions.…”
Section: Teaching and Learning Methodsmentioning
confidence: 99%